(untitled) (Journal of Scientific Research, 2014)
As natural streams enter reservoirs, the streams flow depth increases and the flow velocity decreases. Itdecreases the sediment transport capacity of the stream and causes settling. Numerous methods have been planned to control the sedimentation process. These may include catchment’s management, flushing, sluicing etc. Flushing is used to erode previously deposited sediments. When outlet is opened the sediment in the vicinity of the outlet openings is scoured and a funnel shaped crater is created.In this research experimental studywas performed to investigatethe effect of localized vibrations in the sediment layers on the dimensions of the flushing cone. For this purpose laboratory test was carried out under different hydraulic conditions such as five discharges of 0.23, 0.53, 1.21, 1.53 and 2.1 lit/s with bottom outlets with diameters of 1 and 2 inch. Using the vibrator machine mounted in the reservoir and close to the bottom outlet, different frequencies(e.g. 20, 35 and 50 Hz) have been applied for the deposited sediment in the vicinity of the outlet. The results showthat, the dimension offlushing cone significantly increaseddue tovibrations. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.17236 J. Sci. Res. 6 (3), 475-485 (2014)